Politicians’ Luck of the Draw: Evidence from the Spanish Christmas Lottery - Bagues, Manuel; Esteve-Volart, Berta (Journal of Political Economy, 2016)
Incumbent politicians tend to receive more votes when economic conditions are good. In this paper we explore the source of this correlation, exploiting the exceptional evidence provided by the Spanish Christmas Lottery. Because winning tickets are typically sold by one lottery outlet, winners tend to be geographically clustered. This allows us to study the impact of exogenous good economic conditions on voting behavior. We find that incumbents receive significantly more votes in winning provinces. The evidence is consistent with a temporary increase in happiness making voters more lenient toward the incumbent, or with a stronger preference for the status quo.